Aquifer Depletion in the Lower Mississippi River Basin: Challenges and Solutions. (28th December 2017) - Reba, M.L.; Massey, J.H.; Adviento‐Borbe, M.A.; Leslie, D.; Yaeger, M.A.; Anders, M.; Farris, J.
Abstract: The Lower Mississippi River Basin (LMRB) is an internationally‐important region of intensive agricultural crop production that relies heavily on the underlying Mississippi River Valley Alluvial Aquifer (MRVAA) for irrigation. Extensive irrigation coupled with the region's geology have led to significant aquifer decline. The response to the decline has been multi‐faceted. Research related to three responses are highlighted: innovation in rice irrigation, on‐farm reservoirs, and managed aquifer recharge. Irrigated rice grown in Arkansas, which is nearly 50% of annual U.S. rice production, accounts for a significant portion of aquifer withdrawal. As a result, strategies for using less water while maintaining rice yields are being developed. The Rice Stewardship Partnership (RSP) began in 2015 and aims to improve irrigation management in rice lands of the LMRB. Early results from the RSP are presented. Secondly, on‐farm reservoir‐tailwater recovery systems (R‐TWRS) are increasingly used to store abundant surface water in the LMRB. Over 700 R‐TWRS are currently used in rice producing areas of Arkansas. The confining clay layer that overlies the MRVAA in many locations limits rates of aquifer recharge. Locations where the confining layer is thin or non‐existent may provide opportunities for artificial (i.e., managed) recharge. A 10‐m deep excavation pit from a highway project provided an opportunity to measure infiltration rates of the uppermost section of the alluvial aquifer. Findings from this and other studies are used to demonstrate how conservation, off‐season rainfall capture and storage, and managed recharge are being investigated as means to reduce the on‐going decline of the alluvial aquifer that is both economically and ecologically important to the LMRB.